2020
DOI: 10.1101/2020.03.15.20036566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced dengue incidence following deployments of Wolbachia-infected Aedes aegypti in Yogyakarta, Indonesia: a quasi-experimental trial using controlled interrupted time series analysis

Abstract: Background: Ae. aegypti mosquitoes stably transfected with the intracellular bacterium Wolbachia pipientis (wMel strain) have been deployed for the biocontrol of dengue and related arboviral diseases in multiple countries. Field releases in northern Australia have previously demonstrated near elimination of local dengue transmission from Wolbachia-treated communities, and pilot studies in Indonesia have demonstrated the feasibility and acceptability of the method. We conducted a quasi-experimental trial to eva… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Furthermore, recent field trials demonstrated that deployment of the wMel strain into local Ae. aegypti populations can result in a reduction of local dengue transmission [16,17]. Despite the effectiveness of Wolbachia's viral protection, the mechanism(s) that underlies the ability of Wolbachia to control the virus replication is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent field trials demonstrated that deployment of the wMel strain into local Ae. aegypti populations can result in a reduction of local dengue transmission [16,17]. Despite the effectiveness of Wolbachia's viral protection, the mechanism(s) that underlies the ability of Wolbachia to control the virus replication is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogen blocking effects of some Wolbachia strains form the basis of mosquito release programs to reduce dengue transmission (Figure 1B). When natural Aedes aegypti populations carry the wMel or wAlbB Wolbachia strains at a high frequency, this reduces the vector competence of the population, resulting in fewer dengue cases (Ryan et al, 2019, Nazni et al, 2019, Indriani et al, 2020. Wolbachia infections do not always provide protection against pathogens, and the strength of blocking depends on the pathogen (Teixeira et al, 2008), insect host (Lu et al, 2012), Wolbachia strain (Osborne et al, 2009, Ferguson et al, 2015 and environmental conditions (Murdock et al, 2014, Chrostek et al, 2020, Mancini et al, 2020a, Caragata et al, 2013.…”
Section: Pathogen Blockingmentioning
confidence: 99%
“…Importantly, the Wolbachia strains in Ae. aegypti that are being released into the field, including wMel, have an overall suppressive effect on dengue transmission, both in laboratory (Ferguson et al, 2015, Carrington et al, 2017 and field trials (O'Neill et al, 2018, Ryan et al, 2019, Nazni et al, 2019, Indriani et al, 2020. However, given that pathogen blocking by Wolbachia is rarely complete, it is important to consider this variability when planning releases of Wolbachia-infected mosquitoes.…”
Section: Pathogen Blockingmentioning
confidence: 99%
“…aegypti populations. 1517 A recently completed cluster randomised trial of w Mel Wolbachia deployments in Yogyakarta, Indonesia, conclusively demonstrated the efficacy of the method, with a 77% reduction in dengue incidence in Wolbachia -treated neighbourhoods compared to untreated areas. 18 The Yogyakarta CRT included chikungunya and Zika as secondary endpoints, but insufficient cases were detected to permit an evaluation of efficacy against these arboviruses.…”
Section: Introductionmentioning
confidence: 98%